THE CONCEPT OF POST-SOVIET HABITUS: INSTITUTIONAL AND VALUE DIMENSIONS - Kyselova, V. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
The article justifies the heuristic potential of the post-Soviet habitus concept as a theoretical alternative and an analytical tool for investigating the internal factors that determine the specifics of the state's political process. Also a two-level conceptualization of the Post-Soviet habitus through institutional and value dimensions is presented. The concept is extrapolated on the example of Ukraine: the heterogeneity of the Post-Soviet habitus is considered as the instrument for mobilizing the collective identity within the specific conditions of a hybrid armed conflict.